Magnetic actuated pH-responsive hydrogel-based soft micro-robot for targeted drug delivery - Li, Hao; Go, Gwangjun; Ko, Seong Yong; Park, Jong-Oh; Park, Sukho (Smart materials and structures, 2016)
For drug delivery in cancer therapy, various stimuli-responsive hydrogel-based micro-devices have been studied with great interest. Here, we present a new concept for a hybrid actuated soft microrobot targeted drug delivery. The proposed soft microrobot consists of a hydrogel bilayer structure of 2-hydroxyethyl methacrylate (PHEMA) and poly (ethylene glycol) acrylate (PEGDA) with iron (II, III) oxide particles (Fe3O4). The PHEMA layer as a pH-responsive gel is used for a trapping and unfolding motion of the soft microrobot in pH-varying solution, and the PEGDA-with-Fe3O4 layer is employed for the locomotion of the soft microrobot in the magnetic field. The bilayer soft microrobot was fabricated by a conventional photolithography procedure and its characteristics were analyzed and presented. To evaluate the trapping performance and the motility of the soft microrobot, test solutions with different pH values and an electromagnetic actuation (EMA) system were used. First, the soft microrobot showed its full trapping motion at about pH 9.58 and its unfolding motion at about pH 2.6. Second, the soft microrobot showed a moving velocity of about 600 m s−1 through the generated magnetic field of the EMA system. Finally, we fabricated the real anti-cancer drug microbeads (PCL-DTX) and executed the cytotoxicity test using the mammary carcinoma cells (4T1). The viability of the 4T1 cells treated with the proposed microrobot and the PCL-DTX microbeads decreased to 70.25 1.52%. The result demonstrated that the soft microrobot can be moved to a target position by the EMA system and can release a small amount of beads by the pH variation and the robot exhibited no toxicity to the cells. In the future, we expect that the proposed soft microrobot can be applied to a new tumor-therapeutic tool that can move to a target tumor and release anti-tumor drugs.